KAJIAN FAKTOR IKLIM TERHADAP DINAMIKA POPULASI Pyricularia oryzae PADA BEBERAPA VARIETAS PADI SAWAH (Oryza sativa) - Sopialena . (Universitas 17 Agustus 1945 Samarinda, 2015)
Study On Climate Factor Pyricularia oryzae Population Dynamics Of Some Variety Rice Field Rice (Oryza sativa). The research was conducted in June-September 2015 in the district of North Samarinda. The purpose of this study was to determine the climatic factors (temperature, humidity and rainfall) the most dominant on the rate of broad patches, the rate of infection of the pathogen P. intensity of the attacks and the number of spores of P. oryzae oryzae on rice varieties of rice (Inpari7, Ciherang and Cibogo) and to determine the effect of the number of spores of P. oryzae against pathogen attack intensity of P. oryzae on rice varieties of rice (Inpari7, Ciherang and Cibogo) in the district of North Samarinda. The parameters used in this study are climatic factors (humidity, temperature and rainfall) in the field, the extensive development of the disease spots of blast, the intensity of the attack and the number of pathogenic P. oryzae spores of P. oryzae.The results showed that the climatic factors influencing the development of extensive patches of blast disease, the intensity of the attack and the number of pathogenic P. oryzae spores of P. oryzae. Inpari7 varieties are more susceptible than Ciherang and Cibogo seen extensive development of the high spots of blast disease, the intensity of the attack and the number of pathogenic P. oryzae spores of P. oryzae at the beginning of the first week after planting.